Office 2010 just the steps for dummies - Marmel, Elaine J. (--For dummies., 2010)
"...How to convert older documents to Word 2010 ; Steps for printing documents ; Tips for working with Excel cells ; How to create formulas ; Elements you can add to a PowerPoint slide ; How to create an e-mail distribution list ; How to work in Backstage View..."--P. [4] of cover.